Tribological response of waste tire rubber as micro-fillers in automotive brake lining materials - Anand Pai; Sayikumar Subramanian; Tribhuvan Sood (Friction)
Abstract Elastomeric materials show promise as potential micro-fillers in brake linings. They can provide vibration damping and acoustic advantages in intermittent and abrupt impact applications such as braking. The elastomeric material can be salvaged from non-biodegradable automotive tires, thereby providing an opportunity to reuse materials that will otherwise be discarded in landfills. Both tribological and thermomechanical performances of the waste tire rubber were assessed to determine their potential for use as micro-fillers in the brake linings of commercial vehicles with a gross weight less than 16 tons. Accordingly, the brake lining materials were fabricated with fine waste tire rubber particulates (WTRPs) as the micro-fillers, phenolic-R resin as the binder, graphite as the dry lubricant, laterite as the co-filler, and coconut coir for natural fiber reinforcement. The effects of increasing the WTRP weight fraction on the brake response of the linings were analyzed, and the different compositions were benchmarked against a commercial brake lining. Mechanical characterization comprising compressive strength, hardness, density, and porosity studies were carried out. Frictional and wear characteristics of the linings were analyzed using a rotary tribometer with simultaneous thermal monitoring. The manufactured lining with 15 wt% WTRPs exhibited a mean friction coefficient of ~0.38, a specific volumetric loss rate of 1,662 µm3/(N·m), and improved thermal response. Using optical microscopy and scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS), wear surface morphology studies compared the relative development of primary and secondary plateaus and revealed the redistribution of wear debris, leading to the stability of the coefficient of friction.